Indoor Air Quality in College Laboratories: Exposure to Airborne Fungi - Giri, Surendra K. (International Journal of Scientific Research in Biological Sciences, 2020)
The present study was undertaken to identify and find out the airborne viable fungi and their concentrations in indoor environment of college laboratories. Air sampling was conducted in Chemistry, Zoology, Botany, and Geology laboratories by using Hi-Air Sampler (Hi-media LA-002); two media strips were used for isolation of airborne fungi (PS-290 & PS-640). The average counts of total fungi isolated on two media strips were recorded maximum in chemistry laboratory (4088 CFU/m3), followed by Botany (2681 CFU/m3), Zoology laboratory (2300 CFU/m3), and the lowest recorded in geology laboratory (1622 CFU/m3). While comparing the total CFU counts of isolated fungi on two media strips, the maximum counts were recorded on PS-640 media strips (13618.75 CFU/m3), and (9,637.50 CFU/m3) recorded on PS-290 media strips. In chemistry laboratory total 31 species isolated along with Yeast and Non-sporulating fungi, followed by 29 species from Botany laboratory, 26 from Zoology and only 17 species from Geology laboratory. The total fungal counts of all the fungal species isolated from the studied laboratories were considered and found maximum CFU counts of Curvularia clavata, which is most predominant species followed by the species of Cladosporium herbarum, Curvularia geniculata, Alternaria alternata, Aspergillus niger, Alternaria solani, Curvularia lunata, Yeasts, Aspergillus flavus, Penicillium lutem, Penicillium purpurogenum, Aspergillus fumigatus, Penicillium glabrum, Alternaria brassicicola, Alternaria tenuissima, Curvularia brachyspora, Rhizopus, Mucor, and Cladosporium oxysporum.